2018
DOI: 10.2147/dddt.s167405
|View full text |Cite
|
Sign up to set email alerts
|

Emodin mitigates podocytes apoptosis induced by endoplasmic reticulum stress through the inhibition of the PERK pathway in diabetic nephropathy

Abstract: BackgroundEndoplasmic reticulum stress is associated with podocyte apoptosis in the pathogenesis of diabetic nephropathy (DN). A previous study has demonstrated that emodin has a protective effect in the kidney by suppressing proliferation of mesangial cells and inhibiting the renal tubular epithelial-to-mesenchymal transition. However, the effects of emodin on the podocyte apoptosis in DN and its mechanisms are unknown.AimThis study aimed to explore the effect of emodin on DN model KK-Ay mice and high glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 54 publications
3
49
0
Order By: Relevance
“…Previous studies have shown that the interaction between apoptosis and DN included complex pathways and molecular and confirmed the important role of apoptosis pathways in DN. [41][42][43] The B-cell lymphoma 2 family proteins are central regulators of intracellular apoptotic signaling cascades. In this study, WB showed that increased anti-apoptotic protein Bcl-2, and decreased pro-apoptotic protein Bax and caspase-3 in the curcumin group than the DN group in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the interaction between apoptosis and DN included complex pathways and molecular and confirmed the important role of apoptosis pathways in DN. [41][42][43] The B-cell lymphoma 2 family proteins are central regulators of intracellular apoptotic signaling cascades. In this study, WB showed that increased anti-apoptotic protein Bcl-2, and decreased pro-apoptotic protein Bax and caspase-3 in the curcumin group than the DN group in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The mesangial cells are important component of glomerulus, which can act as the barrier of glomerulus 7 . In addition, mesangial cells can take charge of matrix proteins synthesis, which are the main cells of the glomerular cells 8 …”
Section: Introductionmentioning
confidence: 99%
“…For instance, resveratrol can affect the ER to exert its therapeutic impacts [116]. This story is also similar for curcumin [62], berberine [80], emodin [122] and other natural products. So, it is conspicuous that organelles can be considered as potential targets of these natural products.…”
Section: Regulation Of Mitochondria By Plant-derived Chemicalsmentioning
confidence: 86%